COMPARISON OF CHULA FORMULA WITH STANDARD 21/23 RULE FOR ESTIMATION OF OROTRACHEAL TUBE DEPTH IN INTUBATED ADULT PATIENTS: A SINDH INSTITUTE OF UROLOGY AND TRANSPLANTATION EXPERIENCE - Ramesh Kumar; Haidri, Fakhir Raza; Heeralal; Zafar, Bushra (Journal of Ayub Medical College Abbottabad, 2023)
Background: The proper estimation of depth of the orotracheal tube (OTT) in intubated patients is difficult. Several methods have been developed for proper estimation of the depth of OTT. The purpose of this study was to compare two commonly used formulae (21/23 rule and Chula formula) for proper estimation of depth of OTT in our Pakistani population. Methods: In this randomized interventional study, we included 74 adult patients. The study was conducted in the Intensive care unit of a tertiary care hospital in Karachi, Pakistan, from October 2021 to April 2022. Patients were intubated using either the 21/23 rule (OTT was fixed at 21 cm in females and 23 cm in males from the right incisor) or the Chula formula (OTT was fixed at the right incisor according to the height based formula, (height in cm/10)+4). The distance between the carina and the OTT tip was measured using the digital chest x-ray with a PACS software. Results: A total of 74 patients were intubated in which 32 were intubated using 21/23 rule and 42 were intubated using the Chula formula. Four female patients in 21/23 rule group encountered unsafe distance between the carina and the tip of the OTT (i.e., <2 cm) while no such complications were reported in Chula formula group (p-value 0.031). Conclusion: Chula formula was safe method for OTT placement in our study. Further studies with larger sample size are needed to assess the safety and efficacy of Chula formula for Pakistani Population.